A dynamic spectrally enriched subgrid-scale model for preferential concentration in particle-laden turbulence. (July 2019) - Bassenne, Maxime; Esmaily, Mahdi; Livescu, Daniel; Moin, Parviz; Urzay, Javier
Highlights: A new subgrid-scale model for turbulent velocity fluctuations is proposed. The model provides flow scales smaller than the original grid resolution, is dynamic, and is formulated in physical space. The model improves the prediction of the preferential concentration of particles in large-eddy simulations. Abstract: A new subgrid-scale (SGS) model for turbulent velocity fluctuations is proposed for large-eddy simulations (LES) of dispersed multi-phase flows. The modeled velocity contains scales smaller than the LES grid resolution, thereby enabling the prediction of small-scale phenomena such as the preferential concentration of particles in high-strain regions. The construction of the spectrally enriched velocity field in physical space is made dynamically, and is based on (1) modeling the smallest resolved eddies of sizes comparable to the LES grid size via approximate deconvolution, and (2) reconstructing the SGS fluctuations via non-linear generation of small-scale turbulence. The model does not contain tunable parameters, can be deployed in non-uniform grids, and is applicable to inhomogeneous flows subject to arbitrary boundary conditions. The performance of the model is assessed in LES of isotropic turbulence laden with inertial particles, where improved agreement with direct numerical simulation results is obtained for the statistics of preferential concentration.